ORGANIZATIONAL CULTURE THROUGH A COLLABORATIVE AND PARTICIPATORY OBSERVATION APPROACH IN STRENGTHENING MSMES COMPETITIVENESS TOWARD SUSTAINABLE DEVELOPMENT GOALS (SDGS) (POLITEKNIK LP3I JAKARTA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic growth, employment generation, poverty reduction, and sustainable development. However, increasing global competition, technological disruption, and changing market dynamics require MSMEs to strengthen their organizational capacity and competitiveness. One of the most important strategic factors influencing MSME sustainability is organizational culture. This article examines how a collaborative and participatory observation approach to organizational culture can strengthen MSMEs in improving competitiveness and supporting the achievement of the Sustainable Development Goals (SDGs). The study adopts a qualitative descriptive approach using literature review and conceptual analysis methods. The article explores the relationship between organizational culture, collaboration, participatory practices, organizational learning, innovation, and MSME competitiveness within the framework of sustainable development. The findings indicate that collaborative organizational cultures encourage teamwork, knowledge sharing, innovation, and adaptive capacity, while participatory observation approaches strengthen employee involvement, organizational learning, and inclusive decision-making processes. Furthermore, participatory and collaborative organizational cultures significantly contribute to the achievement of SDGs, particularly SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), SDG 12 (Responsible Consumption and Production), and SDG 17 (Partnerships for the Goals). The study concludes that MSMEs that develop adaptive, collaborative, and participatory organizational cultures are better equipped to achieve sustainable competitiveness and long-term organizational resilience in the modern global economy.